2016
DOI: 10.1080/08959285.2016.1165227
|View full text |Cite
|
Sign up to set email alerts
|

A context-independent situational judgment test to measure prosocial implicit trait policy

Abstract: Human Performance, in press. We gratefully acknowledge Margaret Beier for her help with some of the analyses reported here.Two studies developed and validated a context-independent situational judgment test (SJT) of prosocial implicit trait policy (ITP). The first study developed an SJT based on critical incidents about the prosocial behavior of physicians, lawyers, community service volunteers, and human factors engineers. In a sample of 396 undergraduates, this SJT was internally consistent and correlated si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 38 publications
2
32
0
2
Order By: Relevance
“…Conceptualizing general domain knowledge as an ITP provides a key benefit for establishing construct-related validity because it provides a way to scale individual differences in general domain knowledge according to a construct that has ready implications for theoretical connections with other known constructs such as ability, personality, values, and interests (Lievens & Motowidlo, 2016;Motowidlo & Beier, 2010;Motowidlo, Ghosh, Mendoza, Buchanan, & Lerma, 2016). Depending on what trait is represented in a particular ITP, that ITP can be readily associated with particular personality traits, values, interests, and so on.…”
Section: General Domain Knowledge In the Form Of Implicit Trait Policiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Conceptualizing general domain knowledge as an ITP provides a key benefit for establishing construct-related validity because it provides a way to scale individual differences in general domain knowledge according to a construct that has ready implications for theoretical connections with other known constructs such as ability, personality, values, and interests (Lievens & Motowidlo, 2016;Motowidlo & Beier, 2010;Motowidlo, Ghosh, Mendoza, Buchanan, & Lerma, 2016). Depending on what trait is represented in a particular ITP, that ITP can be readily associated with particular personality traits, values, interests, and so on.…”
Section: General Domain Knowledge In the Form Of Implicit Trait Policiesmentioning
confidence: 99%
“…Depending on what trait is represented in a particular ITP, that ITP can be readily associated with particular personality traits, values, interests, and so on. For instance, ITP for prosociality is theoretically and empirically associated with individual differences in agreeableness, conscientiousness, benevolent values, emotional intelligence in the form of both understanding and management, social interests, and (negatively) with relativistic ethical ideology (Motowidlo et al, 2016;Motowidlo, Kell, Martin-Raugh, & Ghosh, 2017). As these traits are theoretically presumed to be antecedents of prosocial ITP, they lend themselves to tests of theory-driven connections between procedural knowledge measured by SJTs with interpersonal content, prosocial ITP, and these traits.…”
Section: General Domain Knowledge In the Form Of Implicit Trait Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Karim et al (2009) in the study on personality and internet facility misuse also found that individuals with high agreeableness personality are less likely to engage in unethical and fraudulent behaviour, and high agreeableness is considered a good predictor of ethical predisposition. Agreeableness also has been mentioned as an important determinant of prosocial behaviour and volunteerism and correlates significantly with benevolent values (Motowidlo, Ghosh, Mendoza, Buchanan, & Lerma, 2016). Individuals higher on agreeableness make more social investments in work, family, religion, and other prosocial activities (Saadullah & Bailey, 2014).…”
Section: Agreeablenessmentioning
confidence: 99%
“…It should result in more generic SJTs, thereby increasing their applicability across jobs and settings. For instance, in Motowidlo, Ghosh, Mendoza, Buchanen, and Lerma (2015), an SJT was developed to measure general domain knowledge about the utility of prosocial action across work settings that combined items about prosocial and antisocial action in four different professional occupations (law, medicine, community service volunteering, and human factors engineering). Results suggested that this "generic " SJT can predict prosocial behavior in occupational and social settings very different from those reflected in the situational item content.…”
Section: Sjts As General Domain Knowledge Measures: Conceptual and Prmentioning
confidence: 99%